Idārah Tanfīdz Barnāmaj Ta’līm Al Lughah Al-‘Arabiyah Litarqiyah Kafāah Al Lughah - Aldzakhiroh, Nilna; Nopriansyah, Beri; Arifa, Zakiyah (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
Management of implementing the Arabic language learning program at the Al-Muhibbin Islamic Boarding School is a planned process. Because considering the current situation where Arabic has become a necessity for today's society in order to be able to keep up with changing times which are increasingly global and not to be left behind by other countries. Therefore, Arabic language learning programs are very important. This research discusses the management of implementing the Arabic language learning program at the Al-Muhibbin Islamic Boarding School. This research uses a qualitative descriptive method, and data collection is carried out by observation, interviews, and documentation. The results of this research indicate that the implementation of the Arabic language learning program at the Al-Muhibbin Islamic Boarding School is going well. There are two Arabic language learning programs at this Islamic boarding school, namely main activities and additional activities. The main activity in this program is classroom learning. This activity goes through three stages, namely introduction, core activities, and closing activities. Activities are held at 14.00-16.00 and 20.00-22.00. Meanwhile, additional activities are divided into daily activities, namely additional mufrodat and muhadasah al-yaumiyah. The weekly activity is muhadhoroh. The annual activities are FASTABIN and rihlah lughoh. Overall, the management of the implementation of the Arabic language learning program at the Al-Muhibbin Islamic Boarding School reflects a strong commitment to providing useful experiences for the students to improve their Arabic language skills and understanding of religion as evidenced by their enthusiasm when participating in this program, their communication practices using Arabic.